Assessment of functional indicators in children with class II Malocclusion with normal, and impaired external respiratory function assessed with spirometry - Drohomyretska, М. С.; Sadek , Абу Сулейман Мохаммед (Actual Dentistry, 2022)
Background. Class II malocclusion is one of the most common problems in orthodontic practice and is accompanied by certain morphological, functional, and aesthetic changes: a violation of the dynamic balance of muscles of a peri-oral area and tongue, which affects many functions of the child: there are disorders of external breathing, speech, chewing and swallowing functions. Among vital functions, breathing can be called one of the most important, because the exchange ofair between a living being, and the external atmosphere is necessary to meet the metabolic needs of the body. During the respiratory process, the tissues of the oral cavity are the first structures that come into contact with the air moving to the upper respiratory tract. Thus, a malocclusion, especially in Class II with retrognathia mandible, can lead to narrowing of the upper respiratory tract. And these changes, in turn, can adversely affect lung function. Therefore, the correction of retrognathia mandible in Class II Malocclusion by functional appliances can have a beneficial effect on the functions of the lower respiratory tract. Objective. Study of functional (cephalometric and spirometric indicators) in patients aged 7–13 years with skeletal class II malocclusion with normal and impaired function of external breathing. Research methods. Cephalometric analysis of the assessment of the position of the jaws and upper respiratory tract (nasopharynx, oropharynx and hypopharynx) by the McNamara method. Spirometric analysis to assess lung function. Results. The conducted study did not reveal a correlation between the types of jaw growth profile and the volume of the upper respiratory tract in all experimental groups compared to patients in the control group. We also found a low correlation between the nasopharyngeal respiratory function and the position of the lower jaw in different types of class II malocclusion, while changes in the position of the lower jaw significantly affect the volume of the oropharynx and hypopharynx. We found a worsening of the results of FVC, FEV1, IT%(FEV1/FVC) PEF and FEF25–75% in children with narrowing of the upper airways (I-1 and II-1 subgroups) compared to all I-2 and II-2 subgroups and control group (p < 0.05), In addition, a non-significant (p > 0.05) decrease in spirometric measurements was noted in children without narrowing of the upper respiratory tract (I-2, II-2 subgroups) compared to control group. Conclusions. In order to determine the effectiveness of orthodontic treatment of class II malocclusion, it is necessary to conduct a cephalometric and spirometric study before and after the treatment to determine its effectiveness.